Media Video Nicos Weg dalam Meningkatkan Kemampuan Menyimak Bahasa Jerman - Andi Nur Sailal Armi; Syamsu Rijal (Phonologie : Journal of Language and Literature, 2023)
Abstract. This research is a classroomaction research which consists of two cycles. The purpose of this study was to determine the planning, process and results of using Nicos Weg's video media in improving the German listening skills of class XI IPS 2 students of SMA Negeri 1 Bone. The data in this study consisted of two types, namely: quantitative data and qualitative data. Qualitative data were obtained through observation and quantitative data obtained through the results of the listening ability test cycle I and cycle II. The results of the data analysis showed that the listening ability score obtained by students in the first cycle was 76.28%, while in the second cycle it was 87.57%. These results indicate that the use of Nicos Weg's video media can improve the German listening skills of class XI IPS 2 students of SMA Negeri 1 Bone.Keyword: Listening Ability,Nicos Weg, Germany